APPLICATION OF THE WINDOW SHOPPING LEARNING MODEL ON PAWARTA MATERIAL TO IMPROVE THE WRITING SKILLS OF CLASS VIII STUDENTS AT SMPN 22 PURWOREJO - Natasya Izzati Nabila; Herlina Setyowati (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2026)
This study aims to improve the news text (pawarta) writing skills of eighth-grade students at SMPN 22 Purworejo through the application of the window shopping learning model. The background of this research is the low writing skills of students, particularly in understanding the structure, elements, and proper use of the Javanese language. The method used in this study is Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. The research subjects were 28 students. Data were obtained through observation, writing tests (pretest and posttest), and documentation, with instruments including observation sheets and a writing assessment rubric covering content completeness, text structure, language use, and creativity. The results of the study showed a significant increase in the average score from 59.1 in cycle I to 80.5 in cycle II, with more than 85% of students reaching the Learning Stage Mastery Criteria (KKTP). In addition to improving learning outcomes, this model encouraged active student participation in discussions, group collaboration, and the ability to give and receive feedback. The conclusion of this study emphasizes that the window shopping learning model is effective in improving students’ ability to write news texts, while also creating an interactive and collaborative learning atmosphere.